2013
DOI: 10.5402/2013/689564
|View full text |Cite
|
Sign up to set email alerts
|

A New Insight into the Morphology of the Human Liver: A Cadaveric Study

Abstract: Background. Day to day advances in the fields of radiology like sonography and CT need to revive interest in the cadaveric study of morphological features of liver, as the accessory fissures are a potential source of diagnostic errors. Accessory fissures vary from single to multiple over different parts of the liver. Aim. In the present study the morphological features of human liver specimens were evaluated by macroscopic examination and morphometric analysis. Methods. The study was conducted on 58 specimens … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 5 publications
0
15
0
Order By: Relevance
“…Joshi et.al., [12] reported a higher incidence of accessory fissures in both caudate lobe and quadrate lobe to be 18% and 20% respectively which is much higher when compared to the present study. Sunitha Vinnakota [15] reported the highest incidence of accessory fissures on the inferior surface of the livers to be 53.44%. and quadrate lobe be 35.48%.…”
Section: Discussionmentioning
confidence: 99%
“…Joshi et.al., [12] reported a higher incidence of accessory fissures in both caudate lobe and quadrate lobe to be 18% and 20% respectively which is much higher when compared to the present study. Sunitha Vinnakota [15] reported the highest incidence of accessory fissures on the inferior surface of the livers to be 53.44%. and quadrate lobe be 35.48%.…”
Section: Discussionmentioning
confidence: 99%
“…It seems that they are more frequently encountered on the right lobe, followed by quadrate lobe [6]. Interestingly, they can be seen in 6-53% of cases, although, the data about this anomaly is not abundantly present in the literature [6,7]. ALF are in 47% multiple (from 2 to 6) [8,9].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, one liver had accessory fissures on both right and left lobes (figure 8) and another liver had accessory fissure on the left lobe (figure 7). Vinnakota et al [23] studied 54 liver specimens and found 10 livers with right lobe accessory fissures and six livers with left lobe accessory fissures. Mamatha Y et al [24] found 10% livers with right and left lobe accessory fissures.…”
Section: Discussionmentioning
confidence: 99%